Pengaruh Pupuk Organik Limbah Jamur Merang dan Pupuk Hayati Terhadap Pertumbuhan dan Hasil Tanaman Kedelai (Glycine max L. Merril) Varietas Grobogan - Pradana, Haria; Subardja, Vera Oktavia; Pirngadi, Kasdi (JURNAL AGROPLASMA, 2024)
The neednutrients in the soil isimportantfor the successful growth and yield of soybean. Organic fertilizer of merang mushroom waste and types of biological fertilizers are one of the efforts to improve soil fertility and provide sufficient nutrients in the soil. The purpose of this study was to determine the effect of the interaction between organic fertilizer of merang mushroom and type of biological fertilizers on the growth and yield of soybean plants (Glycine maxL. Merril) Grobogan Variety. This research was conducted at Experimental Farm of the Campus 1 Faculty of Agriculture, Singaperbangsa University of Karawang, located in Puseurjaya Village, East Telukjambe Subdistrict, Karawang Distric, West Januari. The experiment was conducted from Januari  to April 2024. The research method was used randomized block design (RBD), factorial with two factors. The first factor was the application of organic fertilizer of merang mushroom waste (M) with 3 levels, The second factor was the application of biological fertilizer (P) with 4 levels. There were 12 treatments that will be 3 replications, so there were 36 experimental units. Each unit has 3 sampleplants. The effect of treatment was analyzed by analyzed of variance and if the F test at 5% level was significant, then DMRT (Duncan Multiple Range Test). The results showed that there where interaction between organic fertilizer of merang mushroom waste and the type of biofertilizer on the parameters of plant height  14, 21, 28, 35 and 42 days after planting (dap), number of trifoliate leaves  21, 28, 35 and 42 dap, stem diameter 42 dap, root length, root nodules, number of pods,  the number of seeds, but they were not interaction on the parameters of root wet weight, root dry weight, seed weight per 100 grains and yield of seed weight. Keywords: soybean, nutrient, organic fertilizer, biofertilizer